A qualitative study of family caregivers’ coping strategies of looking after people with dementia in China - Xiuxiang, Zhang (J Res Nurs, 2020)
BACKGROUND AND AIMS: Globally, two thirds of people with dementia are cared for by their families or friends. Family caregivers’ coping strategies of managing the caregiving burden of dementia have been studied widely in western literature. However, few attempts have been made to explore the experience of family caregivers’ coping strategies in China. The aim of this study was to explore the family caregivers’ coping strategies when caring for people with dementia in one city in the province of Shandong, China. METHODS: Fourteen family caregivers were individually interviewed, and interpretative phenomenological analysis was used to identify themes within different family members. RESULTS: Four key themes were found: (a) being filial; (b) changing self and self-care; (c) seeking help; and (d) having hope and continuing life. CONCLUSION: The study illustrates the different strategies developed by family members in order to cope with their new roles when caring for a relative who has dementia. It shows that cultural belief of filial piety plays a large role across these various coping strategies. It highlights how responsibility has been maintained and influenced by the specific sociocultural context. The results provide a useful foundation for developing interventions that support family caregivers cope with the burden of caring in this population.